Evolution of surface mechanical properties and microstructure of Ti 6Al 4V alloy induced by electropulsing-assisted ultrasonic surface rolling process - Wang, Haibo; Song, Guolin; Tang, Guoyi (Journal of alloys and compounds, 2016)
Effect of electropulsing-assisted ultrasonic surface rolling process (EP-USRP) on surface mechanical properties and microstructure of Ti-6Al-4V alloy was investigated. Compared with the original ultrasonic surface rolling process (USRP), the introduction of electropulsing with optimal parameters can effectively facilitate surface cracks healing, improve surface microhardness and wear resistance. In addition, the residual compressive stress is further enhanced under EP-USRP. Rapid improvement of the surface mechanical properties should be attributed to the ultra-refined grains and enhanced plastic deformation caused by the coupling effect of USRP and electropulsing. High strain rate given by USRP, the accelerated dislocation mobility and atom diffusion induced by electropulsing are likely the primary intrinsic reasons for the observed phenomena.